Etyka w działalności organizacji pozarządowych - Lichwiarz, Justyna (Annales. Etyka w Życiu Gospodarczym, 2011)
NGOs are an important component of democratic society. The specificity of the system based on the participation of citizens provides the possibility of association of individuals to perform the duties of a socially useful. Isolation of the third sector, despite its unquestioned role in society, carries the risk of fraud-related manufacturing sphere of disposing of public funds and foreign, communicated through competitions. Any formulated opinions were based on existing literature and on experience, systematic observations using a questionnaire. The article raised questions were formal, reflecting the legal position and market the third sector and ethical issues, revealing the dilemmas posed to the members of the organization. The most valuable source allows the evaluation of NGO, are according to the author's informal discussions. Indeed, they reveal the real motives that lead individuals to activity in the third sector, which is to be ideologically-profit area. In the course of scientific inquiry, the hypothesis was formulated concerning the relationship between the systems of organization leaders and their tendency to dispose of property unfairly. Moreover, the observed phenomenon of formation of categories of nouveau riche who are using its intellectual potential, they see the organization of project activities, multiplying the sources of private capital.